Analisis Kesadaran Masyarakat Desa Tanjung Gusta pada Masa Pandemi Covid-19 dalam Mematuhi Protokol Kesehatan - Sudianto Sudianto; Siti Fatimah; Yusuf Yusuf; Arya Neta Adinda Jambak (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This article aims to discuss public awareness in Tanjung Gusta village during the Covid-19 pandemic in complying with health protokols. Data collection techniques by means of interviews, observation and documentation. The results showed that the community was not disciplined in implementing health protokols such as not wearing masks, not maintaining distance, and lack of facilities for washing hands in public facilities. The research activity took place from July 7, 2021 to August 04, 2021, the research was carried out in Tanjung Gusta Village, Deli Serdang Regency. The efforts made to make the public aware of the importance of following the Covid-19 prevention health protokol in Tanjung Gusta Village were carried out through socialization of maintaining health during the Covid-19 pandemic, avoiding crowds and not forgetting to wear masks. Community service activities in Tanjung Gusta Village helped increase public awareness for healthy living by wearing masks, reducing activities outside the home, avoiding touching crowds, and using hand sanitizer.